1993
DOI: 10.1016/0735-1097(93)90222-m
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rebound coagulation phenomenon after cessation of a 4-hour infusion of a specific thrombin inhibitor in patients with unstable angina pectoris

Abstract: In patients with unstable angina, argatroban inhibits clotting (aPTT prolongation) and thrombin activity toward fibrinogen (fibrinopeptide A decrease), but in vivo thrombin (thrombin-antithrombin III complex) formation is not suppressed. However, cessation of infusion is associated with rebound thrombin (thrombin-antithrombin III complex) generation and with an early dose-related recurrence of unstable angina. Although the mechanism of this clinical and biochemical rebound phenomenon remains to be determined, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(62 citation statements)
references
References 38 publications
5
55
2
Order By: Relevance
“…Treatment with inogatran led to a dose dependent increase in activated partial thromboplastin time. In our study, activated partial thromboplastin time levels were comparable to those reached in a study using the low molecular mass thrombin inhibitor argatroban [16] , but low as compared to those reached in a similar study using desulphato-hirudin [17] . Since inogatran, argatroban, efegatran and desulphato-hirudin have never been compared in a clinical trial, differences between these compounds must be discussed with caution.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Treatment with inogatran led to a dose dependent increase in activated partial thromboplastin time. In our study, activated partial thromboplastin time levels were comparable to those reached in a study using the low molecular mass thrombin inhibitor argatroban [16] , but low as compared to those reached in a similar study using desulphato-hirudin [17] . Since inogatran, argatroban, efegatran and desulphato-hirudin have never been compared in a clinical trial, differences between these compounds must be discussed with caution.…”
Section: Discussionsupporting
confidence: 61%
“…Inogatran has once previously been evaluated in a small study in patients with unstable coronary artery disease, in which a tendency towards a reduction in thrombinantithrombin and prothrombin fragments 1 and 2 was seen [36] . Infusion of argatroban has, in a previous study, been shown to reduce the levels of fibrinopeptide A, but not thrombin-antithrombin [16] . Likewise, desulphatohirudin has, compared with heparin, proved to be more promising as a thrombin activity-inhibitor, by a decline in fibrinopeptide A, than a thrombin generationinhibitor, with no decrease in prothrombin fragments 1 and 2 and thrombin-antithrombin [17,27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several trials of direct thrombin inhibitors, there has been a correlation between higher doses and higher rates of rebound events. 9,10 In the GUSTO-I trial, patients experiencing rebound ischemic events had higher aPTT levels during heparin infusion than those who did not experience an event. 2 In the multivariate analysis, patients from North America were more likely to experience a rebound event than those from Europe (odds ratio, 3.28; 95% confidence interval, 2.20 to 4.94).…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Argatroban has also been evaluated in several small, randomized, controlled trials in patients with acute coronary syndromes, but results were inconclusive. [55][56][57] …”
Section: Clinical Trials With Argatrobanmentioning
confidence: 99%